2012
DOI: 10.1371/journal.pone.0030572
|View full text |Cite
|
Sign up to set email alerts
|

Human Tumor Cell Proliferation Evaluated Using Manganese-Enhanced MRI

Abstract: BackgroundTumor cell proliferation can depend on calcium entry across the cell membrane. As a first step toward the development of a non-invasive test of the extent of tumor cell proliferation in vivo, we tested the hypothesis that tumor cell uptake of a calcium surrogate, Mn2+ [measured with manganese-enhanced MRI (MEMRI)], is linked to proliferation rate in vitro.Methodology/Principal FindingsProliferation rates were determined in vitro in three different human tumor cell lines: C918 and OCM-1 human uveal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The Ki-67 (Fig. 5) and MEMRI observations agreed well with a previous report (18) and suggested that the Mn 2þ accumulation in tumors, when evaluated during the early phase (24 hours) after irradiation, reflects cell-cycle alteration and a subsequent decrease in cell proliferation rather than apoptotic alterations.…”
Section: Factors Involved In Mnsupporting
confidence: 90%
See 3 more Smart Citations
“…The Ki-67 (Fig. 5) and MEMRI observations agreed well with a previous report (18) and suggested that the Mn 2þ accumulation in tumors, when evaluated during the early phase (24 hours) after irradiation, reflects cell-cycle alteration and a subsequent decrease in cell proliferation rather than apoptotic alterations.…”
Section: Factors Involved In Mnsupporting
confidence: 90%
“…In previous work, it was reported that Mn 2þ uptake in the tumor is linked to the proliferation rate of tumor cells (18). In our study, the number of Ki-67-positive cells (potential marker of tumor growth activity; refs.…”
Section: Factors Involved In Mnmentioning
confidence: 63%
See 2 more Smart Citations
“…14 The faster growth of the C918 tumors is consistent with the finding that C918 cells have a higher proliferation rate in vitro than OCM-1 cells. 26 Second, the modeling also permits the calculation of tumor growth rate at any time point (equation 2). For example, in Rat 54 ( Fig.…”
Section: Modeling the Growth Of Human Choroidal Melanoma Xenograftsmentioning
confidence: 99%